2005
DOI: 10.1176/appi.ajp.162.12.2376
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Antipanic Activity of Aerobic Exercise

Abstract: Aerobic exercise has an acute antipanic activity in healthy subjects. If the authors' results are confirmed in patients, the optimum intensity and duration of acute exercise for achieving antipanic effects will have to be characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 17 publications
2
53
0
8
Order By: Relevance
“…To date, there has been limited research examining the effect of single bouts of exercise on acute mood symptoms in people with MS, although there is a large body of research examining single bouts of exercise (eg, cycling, walking, resistance training, or aqua aerobics) [10][11][12][13] on acute mood symptoms in the general population. 14 We are aware of one study 15 that examined changes in total mood disturbance (TMD; higher scores indicate worse mood) on the Profile of Mood States (POMS) questionnaire after a single session of cycling exercise in women with MS. That study reported significant reductions in TMD scores 20 and 60 minutes after the single session of cycling exercise.…”
Section: Participantsmentioning
confidence: 99%
“…To date, there has been limited research examining the effect of single bouts of exercise on acute mood symptoms in people with MS, although there is a large body of research examining single bouts of exercise (eg, cycling, walking, resistance training, or aqua aerobics) [10][11][12][13] on acute mood symptoms in the general population. 14 We are aware of one study 15 that examined changes in total mood disturbance (TMD; higher scores indicate worse mood) on the Profile of Mood States (POMS) questionnaire after a single session of cycling exercise in women with MS. That study reported significant reductions in TMD scores 20 and 60 minutes after the single session of cycling exercise.…”
Section: Participantsmentioning
confidence: 99%
“…Araştırma sonuçlarına göre fiziksel aktivitenin depresyon ve anksiyete bozukluklarında etkili tedavi yöntemlerinden biri olduğu, hatta fiziksel aktivitenin depresyon ve anksiyete bozukluklarında en az ilaç tedavisi kadar etkili olabildiği bildirilmiştir (Bingham 2009, Ströhle 2005, Biddle ve Asare 2011, Swan ve Hyland 2012. Aynı zamanda fiziksel aktivite oldukça etkili, uygun maliyetli ve yaygın olarak kullanılan bir yöntem olarak kabul edilmektedir (Ströhle 2005). Özellikle ilaç kullanamayan kişilerde fiziksel aktivite hem düşük maliyeti, hem de ilaç tedavisine göre yan etkisinin az olması nedeniyle oldukça etkili bir tedavi yöntemi olarak kullanılmaktadır (Bingham 2009 Orta düzeyde depresyon üzerine etkisi 3.…”
Section: Wwwcappsyorgunclassified
“…Pojawiają się także interpretacje, zgodnie z którymi aktywność fizyczna wpływa na korzystne kształtowanie się osobowości, nie zaś bezpośrednio na występowanie depresji czy lęku (Hansen, Sundberg, 2017, s. 72). Z drugiej jednak strony, badania przeprowadzone na osobach, u których wywoływano atak paniki poprzez zaaplikowanie pewnego rodzaju cholecystokininy, (CCK-4) pokazały, że trzydziestominutowy wzmożo-ny wysiłek fizyczny przed podaniem substancji wywołującej stany lękowe w znaczący sposób obniża ryzyko wystąpienia napadu paniki po ich podaniu (Strohle et al, 2005;Strohle et al, 2009).…”
Section: Aktywność Fizyczna a Lęk I Depresja Jako Wybrane Aspekty Fununclassified